Comparative analyses of the salivary gland secretomes from related species of the gall midge family Cecidomyiidae - Al-Jbory, Zainab Abdalhussin Ali (Kansas State University, 2018)
The tools for arthropods with sucking-mouth parts to attack hosts are mainly in the saliva. For plant-sucking insects, these salivary secretions are primarily produced in the salivary glands. Secreted proteins (also referred to as salivary gland secretomes) are among the important components in the saliva of sucking insects. Gall midges (Cecidomyiidae), a large family of plant-sucking insects, apparently secrete proteins (some of them are effector proteins) into host tissues, inducing various forms of plant outgrowth (galls). Three major insect pest species in the genera Mayetiola, the stem gall midges, are known to produce saliva that can reprogram plant cells and manipulate the host plant growth, causing serious damage to the plants of small grains. The three pest species are the Hessian fly (Mayetiola destructor), the barley midge (Mayetiola hordei), and the oat midge (Mayetiola avenae). Another economically important species of this gall midge family is the wheat midge (Sitodiplosis mosellana). It is a major insect pest of spring wheat and feeds on wheat heads, causing damage to the developing wheat seeds. A global analysis of the salivary gland secretome of first instar larvae of the Hessian fly, (a member of Mayetiola and) a model species for studying insect-plant interactions, has previously revealed a large number of genes encoding Secreted Salivary Gland Proteins, so called SSGPs. For comparison, we conducted analyses on transcripts encoding SSGPs from salivary glands of the first instar larvae of the wheat midge, barley midge, and oat midge. In the first chapter, a transcriptomic analysis of wheat midge has been conducted. In this analysis, a total of 3,500 cDNA clones were sequenced, and 1,301 high quality sequences were obtained and approximately 25% of the cDNAs (with high quality sequences) encoded SSGPs. The SSGPs were grouped into 97 groups based on sequence homology. Among the SSGP-encoding transcripts, 206 encoded unique proteins with no sequence similarity to any known protein and 29 encoded proteins similar to known proteins including proteases, serpines, thioesterases, ankryins, and feritins. The compositions of SSGP transcripts from the wheat midge were then compared with that of Hessian fly. The analyses have identified many common characteristics between the species. Despite these commonalities, no sequence similarity was found between SSGPs from wheat midge and those from Hessian fly, suggesting that SSGPs from these two insect species perform different functions to manipulate host plants. The second chapter contains results of comparative transcriptomic analyses on the barley and oat midges. A total of 2570 cDNA clones were sequenced from the barley midge, and 743 were high quality cDNA sequences, and the analysis identified 458 cDNA clones encoding SSGPs, of these, 178 encoded unique proteins (also called unigenes). Transcripts encoding SSGPs were grouped into 51 groups based on sequence homology. A total of 3226 cDNA clones were sequenced from oat midge, and 718 cDNA sequences were high quality and used for further analysis. The analysis identified 450 cDNA clones encoding SSGPs. Among the SSGP-encoding transcripts, 194 are unigenes, which were placed into 50 groups. The compositions of SSGP transcripts from the barley and oat midges were then compared with that of Hessian fly. The analysis identified five groups containing 102 (57.3%) unigenes from barley midges and seven groups containing 107 (55.1%) unigenes from oat midges which encode SSGPs that are conserved among the three species. The SSGPs conserved among the three midges are from family one (SSGP-1), family 4 (SSGP-4), family 11 (SSGP-11), and family 71 (SSGP-71). The SSGPs conserved among the three species indicate conserved functions such as a role in plant manipulation. Some SSGP unigenes were found to be conserved between only two species. Specifically, there were eight gene groups which are conserved between two species. Within these eight groups 19 (10.7%) unigenes from the barley midge and 25 (12.9%) unigenes from the oat midge were found to be conserved between only the barley and oat midges, whereas no homologues have been found in the Hessian fly. The remaining unigenes encode SSGPs that are unique to different midge species. The highly divergent SSGP groups that have been identified with no homology among the three midges indicate potential roles of these SSGPs in host specification. Due to the important roles of effector proteins in insect-plant interactions for gall midge species and since no insect effector protein have been identified directly from infested plant tissues so far, I have chosen one of the SSGP family, SSGP-1, which are conserved among all three gall midge species, for further analysis in chapter 4. Members in family SSGP-1 are also the most abundantly expressed at the transcript level. Based on Hessian fly data, family 1 contains seven genes and are named SSGP-1A1, SSGP-1A2, SSGP-1B1, SSGP-1C1, SSGP-1C2, SSGP-1D1, and SSGP-1E1. To detect the presence of these proteins in the infested wheat tissues, and to identify probable targets from wheat that interact with the SSGPs in the feeding site, we have generated and purified recombinant proteins for five of the seven proteins, namely SSGP-1A2, SSGP-1B1, SSGP-1C1, SSGP-1D1, and SSGP-1E1 (since SSGP-1A1 and SSGP-1C2 are very similar to SSGP-1A2 and SSGP-1C1, respectively). Antibodies were produced for the recombinant proteins for western blot analyses and indirect immunostaining. Immunostaining on dissected tissues including salivary glands, guts, and Malpighian tubules from 3-day old larvae, was conducted with antibodies against the five SSGPs, and detected a specific localization of all proteins in salivary glands except SSGP-1E1, which exhibited a weak signal in the foregut, in addition to localization in salivary glands. Western blot analyses demonstrated that these five proteins were expressed in larvae at all stages. The continuous production of these proteins suggests that they play roles in initiation and maintenance in Hessian fly infestation. Consistent with their effector functions, these five proteins were detected for the first time in infested wheat tissues based on western blot analyses. To identify possible target proteins from host plants that interact with SSGP-1 family proteins, in vitro pull-down assays were performed. Putative interacting targets for SSGP-1A2, SSGP-1B1, and SSGP-1C1 have been identified by LC-MS/MS. These putative interaction target proteins included uncharacterized proteins, ribosomal proteins, a lipoxygenase, and a tubulin. Identification of these putative targets provided a base for further confirmation of their interaction with Hessian fly effectors in the future.
Keywords: Gall midge family; Transcriptomic analysis; Family SSGP-1 effectors; Secreted salivary gland proteins (SSGPs)